2020
DOI: 10.1542/peds.2019-2470
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Opioid Misuse and Risky Adolescent Behavior

Abstract: OBJECTIVES: Misuse of opioid medications (ie, using opioids differently than how a doctor prescribed the medication) is common among US adolescents and associated with preventable health consequences (eg, severe respiratory depression, seizures, heart failure, and death).1 New guidelines and recommendations have made providers more attuned to overprescribing and more vigilant about screening for opioid misuse.2 We hypothesized that youth who misused prescription opioids were more likely to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 20 publications
0
33
0
1
Order By: Relevance
“…8 Previous longitudinal studies of administrative claims data also highlight an association between preexisting mental health disorders and new onset of long-term prescription opioid use among adolescents. 9,10 The only existing data on the association of behavioral health problems and nonmedical prescription opioid use in youth are cross-sectional 8,[11][12][13][14] and leave key evidence gaps. First, because the mechanisms of this association could be bidirectional (ie, opioid misuse may result from or lead to other behavioral health problems), 11,14 it is imperative that researchers on this topic apply prospective longitudinal designs that preclude reverse causality explanations.…”
mentioning
confidence: 99%
“…8 Previous longitudinal studies of administrative claims data also highlight an association between preexisting mental health disorders and new onset of long-term prescription opioid use among adolescents. 9,10 The only existing data on the association of behavioral health problems and nonmedical prescription opioid use in youth are cross-sectional 8,[11][12][13][14] and leave key evidence gaps. First, because the mechanisms of this association could be bidirectional (ie, opioid misuse may result from or lead to other behavioral health problems), 11,14 it is imperative that researchers on this topic apply prospective longitudinal designs that preclude reverse causality explanations.…”
mentioning
confidence: 99%
“…We found no evidence that adolescents' past year substance use (tobacco, marijuana, or alcohol) was associated with their lifetime opioid use, nor any evidence that adolescents' prior mental health symptoms of MDD, GAD, or PTSD, nor peer attitudes favorable toward drugs, were predictive of lifetime opioid use. Given that previous studies have consistently reported significant associations between substance use and mental health histories and subsequent opioid use outcomes (Barnett et al, 2019;Griesler et al, 2019;Bhatia et al, 2020;Bonar et al, 2020), further research is warranted to replicate the null findings reported herein.…”
Section: Discussionmentioning
confidence: 56%
“…Extending from the social-ecological model, prior empirical research has found strong evidence for diverse ecological factors predictive of substance use and other related behaviors in adolescence across diverse populations (Arthur et al, 2002;Bränström et al, 2008;Cleveland et al, 2008;Hemphill et al, 2011). Among individual-level predictors, prior tobacco, marijuana, and alcohol use have been consistently identified as salient indicators for subsequent opioid misuse among the general adolescent population (Sung et al, 2005;Back et al, 2010;Palamar et al, 2015;Vaughn et al, 2016;Barnett et al, 2019;Griesler et al, 2019;Bhatia et al, 2020;Bonar et al, 2020;Osborne et al, 2020). Specifically, the odds of reporting having ever misused opioids were three times higher among adolescents with histories of alcohol use (vs. those without), and two times higher among those with histories of cigarette and marijuana use (vs. those without; Barnett et al, 2019).…”
Section: Social-ecological Predictors Of Adolescent Opioid Misusementioning
confidence: 99%
See 2 more Smart Citations